Population replacement of benzimidazole-resistant Haemonchus contortus with susceptible strains: evidence of changes in the resistance status - Muchiut, Sebastián; Fiel, César Alberto; Lirón, Juan Pedro; Lloberas, María Mercedes; Ceriani, Carolina; Lorenzo, Ramiro; Riva, Eliana; Bernat, Gisele Anahí; Cardozo, Patricia Alejandra; Fernández, Silvina; Steffan, Pedro (Springer, 2022)
The spread of anthelmintic resistance (AR) in nematode populations threatens the viability of sheep production systems worldwide, and warrants the adoption of sensitive, practical, and standardized tests to detect AR. The aim of this study was to characterize the replacement of an Haemonchus contortus population resistant to benzimidazoles (BZDs) by a susceptible one, by means of both phenotypic and genotypic techniques. Phenotypic methods to assess BZD resistance included in vivo tests, such as the fecal egg count reduction test (FECRT), and in vitro tests, such as the egg hatch assay (EHA). Additionally, genotypification of polymorphisms associated with BZD resistance by sequencing a fragment of the isotype 1 β-tubulin gene was carried out. The initial, BZD-resistant population (initial Balcarce population) exhibited an egg count reduction (ECR) of 59.3%. Following refugium replacement, the final population (final Balcarce population) exhibited an ECR of 95.2%. For the initial Balcarce population, the median effective dose (ED50) for the EHA was 0.607 μg thiabendazole (TBZ)/mL, with a rate of eclosion at a discriminating dose (EDD) of 0.1 μg TBZ/mL of 76.73%. For the final Balcarce population, ED50 was 0.02 μg TBZ/mL, and EDD was 1.97%. In the initial population, 93% of the analyzed individuals exhibited genotypic combinations associated with BZD resistance (53% Phe/Phe167–Tyr/Tyr200, 37% Phe/Tyr167–Phe/Tyr200, and 3% Phe/Tyr167–Glu/Leu198). Conversely, no combination associated with resistance was found in individuals from the final population. All of the tests were useful for detecting AR to BZDs. The results from the genetic and phenotypical studies were consistent, and the resulting information greatly aided in interpreting the outcomes of the population replacement and the potential impact of this strategy on management of AR.